Successful task shifting: a mixed-methods cross-sectional evaluation of an emergency obstetric care program to increase access to cesarean sections in rural Nepal - Rita Thapa Budhathoki; Abigail G. Knoble; Suresh Tamang; Bal Sundar Chansi Shrestha; Arpana BC Kalaunee; Indra Rai; Bikash Shrestha; Pravin Paudel; Ruma Rajbhandari; Archana Amatya (Global Health Action)
Background Direct obstetric causes of maternal mortality account for approximately 86% of all global maternal deaths. In Nepal, 12% of all deaths of women of reproductive age are due to preventable obstetric complications in significant part due to the limited distribution and skill level of human resources. Objectives To address this, the Advanced Skilled Birth Attendant (ASBA) task-shifting initiative was developed to train medical officers to perform Cesarean sections (CSs) and manage obstetric emergencies in Nepal. Until now, there has been limited study of the program’s efficacy. Methods A survey targeting all 234 ASBA graduates resulted in 93 usable surveys for multivariate regression. Additionally, seven rural government hospitals with ASBA graduates were selected for 13 in-depth interviews and 6 focus group discussions. Results were then triangulated. Results Immediately after training, 92.7% of ASBA graduates reported performing CSs, with the majority (65.6%) continuing to perform CSs today. Of the ASBAs not performing CSs, 51.7% could be explained by the lack of a functional operating theater, despite being at hospitals expected to provide CSs. ASBAs were significantly more likely to be performing CSs with a family physician or another ASBA present (p < 0.001; p < 0.001). Their work was perceived to increase the use of services, improve access, reduce out-referrals, and reduce the burden of CSs on any one staff member. Conclusions The ASBA program successfully reduces human resource shortages, expands the provision of life-saving Cesarean section, and improves the working conditions in rural hospitals within the LMIC setting.